Gentamicin-Ascorbic Acid Encapsulated in Chitosan Nanoparticles Improved In Vitro Antimicrobial Activity and Minimized Cytotoxicity - Mohamed A. Abdel-Hakeem; Ahmed I. Abdel Maksoud; Mohammed Abdullah Aladhadh; Khalid Abdulrahman Almuryif; Rafaat M. Elsanhoty; Dalia Elebeedy (MDPI AG, 2022)
Nano-drug delivery is a promising tactic to enhance the activity and minimize the cytotoxicity of antimicrobial drugs. In the current study, chitosan nanoparticles (CSNPs) were used as a carrier for the delivery of gentamicin sulfate (GM) and ascorbic acid (AA). The particles were synthesized by ionotropic gelation method and characterized by FT-IR, Zeta potential, and transmission electron microscope imaging. The obtained particles were evaluated for their in vitro antimicrobial activity and cytotoxicity. The prepared particles (GM-AA-CSNPs) under the optimal condition of 4:1:1 of chitosan to drug ratio showed encapsulation efficiency and loading capacities of 89% and 22%, respectively. Regarding biological activities, GM-AA-CSNPs showed a lower minimum inhibitory concentration (MIC) than free gentamicin sulfate and GMCSNPs mixture without presenting cytotoxicity against normal cells (HSF). Moreover, the GM-AA-CSNPs did not exhibit hemolytic activity. These results highlight that the GM-AA-CSNPs are confirmed as a hopeful formula for future investigations on the development of antimicrobial preparations.